Leveraging the wheat germ cell-free protein synthesis system to accelerate malaria vaccine development. (February 2021) - Kanoi, Bernard N.; Nagaoka, Hikaru; Morita, Masayuki; Tsuboi, Takafumi; Takashima, Eizo
Abstract: Vaccines against infectious diseases have had great successes in the history of public health. Major breakthroughs have occurred in the development of vaccine-based interventions against viral and bacterial pathogens through the application of classical vaccine design strategies. In contrast the development of a malaria vaccine has been slow. Plasmodium falciparum malaria affects millions of people with nearly half of the world population at risk of infection. Decades of dedicated research has taught us that developing an effective vaccine will be time consuming, challenging, and expensive. Nevertheless, recent advancements such as the optimization of robust protein synthesis platforms, high-throughput immunoscreening approaches, reverse vaccinology, structural design of immunogens, lymphocyte repertoire sequencing, and the utilization of artificial intelligence, have renewed the prospects of an accelerated discovery of the key antigens in malaria. A deeper understanding of the major factors underlying the immunological and molecular mechanisms of malaria might provide a comprehensive approach to identifying novel and highly efficacious vaccines. In this review we discuss progress in novel antigen discoveries that leverage on the wheat germ cell-free protein synthesis system (WGCFS) to accelerate malaria vaccine development. Highlights: An efficacious malaria vaccine is urgently needed. Eukaryotic WGCFS generated P. falciparum recombinant proteins are functionally active. WGCFS and AlphaScreen system are invaluable tools for vaccine discovery by immunoscreening. Reverse vaccinology and WGCFS offers new approaches to vaccine discovery.